William E. Wagner III Sabbatical Report 2013-2014 - William E. Wagner III::::::
The sabbatical supports my work on a co-authored new survey research textbook (estimated to be approximately 450 pages in length when complete) and ancillary materials. The work on this book lies at the intersection of much of my work in the areas of research and in teaching. In research, much of my work is carried out using data that are collected through surveys or secondary data that had been collected by survey methods. Survey research is a major component, naturally, of research methods in the field of sociology, and our course at California State University Channel Islands: SOC 310, Sociological Research Methods.